Mawas Diri sebagai Transformasi Etis-Spiritual dalam Filsafat Damardjati Supadjar - Arif Dzakwanuddin; Agus Darmaji (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This article examines the concept of mawas diri in Damardjati Supadjar’s philosophy as a process of ethical and spiritual self-transformation. The study employs library research using conceptual analysis and philosophical hermeneutics, focusing primarily on Supadjar’s Mawas Diri: Dari “Diri” yang Tanggal ke Diri yang “Terdaftar, Diakui, Disamakan”. The findings demonstrate that mawas diri is not merely a form of psychological introspection, but a spiritual practice through which individuals recognize, discipline, and transform themselves. This process moves from an alienated self dominated by egoistic tendencies toward a reflective and spiritually integrated self that understands its responsibilities as both a servant and vicegerent of God. Such transformation is grounded in an ontological vision of the interconnectedness between the outward and the inward, the beginning and the end, and the origin and destination of life. Epistemologically, mawas diri integrates reason, inner feeling, the heart, and reflection upon the signs of life. Ethically, it cultivates mulat sarira, humility, vigilance, and self-restraint in personal and social relationships. This study argues that Damardjati Supadjar’s concept of mawas diri constitutes a practical philosophy that connects self-knowledge, moral formation, social responsibility, and spiritual orientation toward God.